The Impact of Financial Technology on Advancing Banking Services and Promoting Financial Inclusion in Libya - Etorbi, Mustafa (Universitas Muhammadiyah Surakarta, 2025)
This research examines the impact of Financial Technology (FinTech) on advancing banking services and financial inclusion in Libya. The study aims to foster financial inclusivity and advance fintech development in Libya, relying on the Innovation Diffusion Theory. Utilizing a quantitative approach in this research, data is collected from Libyan bank customers through structured questionnaires and is analyzed using the Statistical Package for Social Sciences (SPSS). The findings of this research support the hypothesis that the adoption of Alternative Payment Methods (APMs) and automation by banks positively impacts financial inclusion and service quality. The results of this study intend to assist policymakers and financial institutions in devising targeted plans to support Libya’s recovery through FinTech, modernizing its banking system, and improving the quality of services offered to citizens. This study informs the debate on developing technology-based mechanisms to tackle the specific banking problems in Libya, improve financial inclusion and assists the key stakeholders by providing them with an elaborate roadmap on enhancing service delivery.